Reactively Loaded Array Pattern Synthesis as a Quadratically Constrained Quadratic Program - Corcoles, Juan (IEEE transactions on antennas and propagation, 2015)
The pattern synthesis problem of maximizing the gain at a scanning direction subject to a maximum sidelobe level for a reactively loaded antenna array is formulated as a quadratically constrained quadratic program (QCQP). This formulation is derived from the scattering matrix and the active element patterns of the array considering both fed and loaded antennas as ports. Since the resulting QCQP is nonconvex, the loads are computed from the solution of the semidefinite relaxation of the problem by forcing the feasibility of the constraints in a meaningful physical sense, i.e., by explicitly imposing passive or purely reactive loads. Numerical results of dipole arrays with various configurations are presented and compared to previous works.